The creative thinking ability of high school student to ecological problem - Nitta Hadiyah; Aminuddin Prahatama Putra; Atiek Winarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Creative thinking in the 21st century is needed to prepare humans to become faithful, productive, innovative and creative individuals and contribute to the life of society, nation, and state. Schools make creative thinking skills one of the graduation competencies of students. This study aims to describe the level and character of students' creative thinking skills in solving ecological problems. The research method is descriptive with a qualitative approach. The research subjects were nine students selected based on the purposive sampling method. Data were analyzed using the triangulation analysis method. The study results used four levels of students' ability to solve problems creatively on the concept of ecology. The level of creative thinking ability of students is dominant at a moderately creative level. Characteristics of the creative thinking ability level of students, namely the creative level, have a high fluency aspect achievement, while flexibility and novelty are classified as moderate. The moderately creative level has a moderate achievement of fluency, flexibility, and novelty aspects, and students with a less creative level have a low achievement of fluency, flexibility, and novelty aspects. These results prove that creative thinking skills still need to be optimized at the high school.Abstrak Berpikir kreatif pada abad 21 dibutuhkan untuk mempersiapkan manusia menjadi pribadi yang beriman, produktif, inovatif dan kreatif serta berkontribusi pada kehidupan masyarakat, berbangsa dan bernegara. Sekolah menjadikan kemampuan berpikir kreatif salah satu kompetensi kelulusan peserta didik. Penelitian ini bertujuan mendeskripsikan tingkat dan karakter kemampuan berpikir kreatif peserta didik dalam menyelesaikan masalah ekologi. Metode penelitian deskriptif dengan pendekatan kualitatif. Subjek penelitian adalah sembilan orang peserta didik yang dipilih berdasarkan metode purposive sampling. Data dianalisis mengunakan metode analysis triagulasi. Hasil penelitian menggunakan empat tingkat kemampuan peserta didik dalam penyelesaian masalah secara kreatif pada konsep ekologi. Tingkat kemampuan berpikir kreatif peserta didik dominan pada tingkat cukup kreatif. Karakteristik tingkatan kemampuan berpikir kreatif peserta didik, yaitu tingkat kreatif memiliki ketercapaian aspek fluency tinggi, sedangkan flexibility dan novelty tergolong sedang. Tingkat cukup kreatif memiliki ketercapaian aspek fluency, flexibility dan novelty tergolong sedang, dan peserta didik tingkat kurang kreatif memiliki ketercapaian aspek fluency, flexibility dan novelty tergolong rendah. Hasil ini membuktikan kemampuan berpikir kreatif masih perlu dioptimalkan di tingkat SMA.